A Toolkit for Modern Life : 53 ways to look after your mind - Hepburn, Emma (London : Greenfinch, 2020)
Most of us are just trying to keep it together, most of the time. In a world where 'busyness' is the norm, it's easy to feel overwhelmed and stressed out. But proactively paying attention to how we feel, and understanding how to respond to our emotions, is the key to looking after our own mental health and wellbeing. In this book, clinical psychologist Dr Emma Hepburn (aka @ThePsychologyMum) uses her warm and witty illustrations to introduce practical tools for your day-to-day mental wellbeing.
Includes index.
Keywords: Self-actualization (Psychology); Stress management; Psychology